Disaster recovery facilities in the main office? - Mohd Idaham, Umar Ong (Faculty of Computer Systems & Software Engineering, 2011)
The main purposes of this article to come with discuss on internal disaster recovery strategy, where by a company have two facilities, the main data centre and their disaster recovery centre. What if we switch the two locations where your main office will house the DR facilities and your data centre is off-site. Most company applied off-site disaster recovery facilities strategy where the off-site location will function as a secondary data centre to replicate their most critical data to a secure and safe location and their main data centre will be at their main office building.